Fatty acid composition of sprat (Sprattus sprattus) and herring (Clupea harengus) in the Baltic Sea as potential prey for salmon (Salmo salar) - Keinänen, Marja; Käkelä, Reijo; Ritvanen, Tiina; Myllylä, Timo; Pönni, Jukka; Vuorinen, Pekka J.
2017